Utilizing the Critical Inclusive Praxis: The voyage of five selected school principals in building inclusive school cultures. (March 2018) - Osiname, Ayodeji Tolulope
This article integrates relevant literature with the lived experiences of five school principals regarding how they utilized different leadership styles to build an inclusive school culture. The conceptual framework – a Critical Inclusive Praxis, including culture, change, leadership, inclusion and challenge – provided a base for the literature and field research. The framework reinforces principals' responsibility to continuously transform the school through reflective, critical and dialogical action in order to nourish and sustain a strong culture. The study shows that it is essential that principals understand the five elements of a Critical Inclusive Praxis and how they intersect to build socially just and democratic schools.